Does lifestyle behaviour trigger cardiovascular risk factors among school-going adolescents in Pakistan? - Jawed, Nida; Safdar, Nilofer Fatimi; Mehdi, Anishta; Inam, Sumera; Shafique, Kashif; Badruddin, Salma (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the association of gender with risk factors for cardiovascular diseases among adolescents. Method: The cross-sectional study was conducted 2016-2019 in low-income schools in Karachi after approval from the ethics review board of Dow University of Health Sciences, and comprised adolescents of both genders aged 11-17 years. Anthropometric measurements and lifestyle behaviours were used to generate risk profile for cardiovascular diseases. Data was analysed using SPSS 16. Results: Of the 1195 subjects, 468(39.2%) were boys and 727(60.8%) were girls. The mean age was 13.9±1.6 years. Mean family size was 5.9±3.64. Overall, 989(91.3%) participants consumed soft drinks, 44(4%) were smokers, 340(48.4%) consumed betel nut, 215(32.9%) Pan, 125(21.2%) Gutka and 9(1.7%) Bidi. Of the total, 867(83.3%) participants were physically less active than recommended, and daily screen time was >2 hours among 513(45.7%) participants. Body mass index and body fat percentage were significantly higher among girls (p<0.05). Higher rates of diastolic and systolic blood pressure and hand grip strength were observed in boys compared to girls (p<0.05). Conclusion: Interventional programmes in schools should emphasise the need for healthy lifestyle behaviours, increased physical activity, good eating habits and smoking cessation. Key Words: CVD risk factors, Adolescents, Lifestyle behaviours, Micronutrients, Pakistan.